2019
DOI: 10.1371/journal.pone.0217430
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on the prevalence of illness and stress and their associated risk factors among educators in Malaysia

Abstract: Background Despite evidence of physical (illness) and mental (stress) health problems, there appears to be a lack of studies or concern regarding occupational safety and health among educators in Malaysia. Objective To review the prevalence of illness, stress, and corresponding risk factors among educators in Malaysia. Method Scopus, ProQuest, PubMed, ScienceDirect, CAB, and other computerized databases were searched according to Preferred Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 41 publications
5
30
1
2
Order By: Relevance
“…These reviews are also coinciding with our study observations. Our study is consistent with the recent observations on work-related MSDs that the most commonly affected body regions were the lower back, neck, and shoulder [ 15 , 19 ], and furthermore, back disorders are considered among the most commonly affected regions in any working industry [ 2 ]. The occupational and demographic factors also influence the prevalence of MSD patterns [ 11 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These reviews are also coinciding with our study observations. Our study is consistent with the recent observations on work-related MSDs that the most commonly affected body regions were the lower back, neck, and shoulder [ 15 , 19 ], and furthermore, back disorders are considered among the most commonly affected regions in any working industry [ 2 ]. The occupational and demographic factors also influence the prevalence of MSD patterns [ 11 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…The current study observed 42.5% annual prevalence of MSDs among the academicians in Saudi Arabia. As compared to previous studies, the present study observes lesser prevalence and change in the ranking of the involvement of body regions may be due to the difference among the participation of various faculties, wide demographics, and different work settings [ 7 , 11 , 15 ]. A previously done study, reported a 12-month NMQ prevalence of 55% WMSDs among faculty members of only Majmaah University with the sample size of 110 [ 16 ], whereas our current study included wide ranges of academic faculties such as nursing, applied medical sciences, pharmacy, dentistry, computer science, science, and engineering from different universities from different demographical regions of Saudi Arabia with larger sample size.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations